2017
DOI: 10.1017/cjn.2017.272
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ultrasonography for Supinator Syndrome: A Case Report

Abstract: Posterior interosseous neuropathy resulting from compression in the radial tunnel, also known as supinator syndrome, is usually diagnosed by clinical assessment and electrodiagnostic testing. 1,2 In the past decade, high-resolution ultrasonography has been applied to aid the diagnosis of entrapment neuropathies such as carpal tunnel syndrome and cubital tunnel syndrome. 3 In this case report, we present how dynamic ultrasonography was used to assist in the diagnosis and treatment of supinator syndrome.A 58-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…We agree with this statement, and in our study, we went further, quantifying the nerve’s angulation and demonstrating the existence of different patterns of nerve deflection with forearm rotation. Chen and Wang demonstrated the clinical application of forearm pronation and supination with HRUS in a case report of supinator syndrome [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We agree with this statement, and in our study, we went further, quantifying the nerve’s angulation and demonstrating the existence of different patterns of nerve deflection with forearm rotation. Chen and Wang demonstrated the clinical application of forearm pronation and supination with HRUS in a case report of supinator syndrome [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [57] reported a 58-year-old man with drop finger for 3-4 months (the muscle strength of the left second and third fingers was 2, and that of the fourth and fifth fingers was 0) diagnosed with supinator syndrome. They performed a single ultrasoundguided PIT with 5 mL D5W to dissect the posterior interosseous nerve.…”
Section: Supinator Syndromementioning
confidence: 99%